Redesign dos diplomas da UTFPR - Silva, Caroline Kêmela (2013)
This work presents a theoretical research about the layout of diplomas and their characteristics, like diagramation, typography and security printing. It compares concepts for diplomas design of other universities, as theoretical basis and image bank. It studies the history and concepts of the Federal Technological University of Paraná, to analyze, from this, their current diplomas, checking their visual and security characteristics and how they could be improved. It researches efficient and visually pleasant features for the development of a new layout for UTFPR’s diplomas. It brings as study result the prototypes of the new layout for UTFPR’s diplomas.